Why Europe matters the case for the European Union - McCormick, John 1954- (Palgrave Macmillan, 2013)
"Critics like to depict the European Union as undemocratic and unpopular, but their arguments are too often based on myths and misunderstandings. This does us all a disservice, and in this period of uncertainty about the future of Europe it is more important than ever that we have a firm grasp of the issues at stake. This powerful new book debunks the misconceptions surrounding the EU and makes a compelling and comprehensive case for the benefits of European integration. It shows how the EU has improved the lives of Europeans in countless ways, and how it has given Europe a powerful presence on the international stage. Guaranteed to illuminate as well as spark debate, this book will appeal to anyone who seeks to better understand what Europe means and why it matters."...Publisher's website